Why reducing socio-environmental externalities of electricity system expansions can boost the development of solar power generation: The case of Chile. (15th March 2021) - Matamala, Carlos; Moreno, Rodrigo; Sauma, Enzo; Calabrese, Jazmine; Osses, Pablo
Highlights: We consider land-use externalities in the first stage of the planning process. We analyze four strategies for coordinating generation and transmission investment. Solar capacity increases when externalities are considered in the system expansion. Regulators have to recognize externalities in the planning problem. Abstract: In recent years, the transition towards low-carbon electricity systems has increased the development of renewable generation and, in turn, of transmission infrastructure. Importantly, developing low-carbon technologies (that are generally located far from load centers) and their associated network infrastructure, may conflict with land uses that are valuable by society (e.g. the presence of national parks, indigenous development, touristic zones, etc.). Appropriately addressing this conflict is key for policy makers and regulators to foster an effective, sustainable, and socially acceptable system expansion. In this context, this work analyzes the effects of accounting for these land-use, socio-environmental externalities on the expansion of the entire power system. For a more effective mitigation of system expansion impacts on land uses, we propose to coordinate the needed investments among the various market participants such as generation developers and network planners. To assess this proposal, we develop a two-stage stochastic program that determines the future generation and network expansions considering both (i) a balance between monetary/investment costs and their corresponding socio-environmental externality costs (derived from the land-use impacts of new electricity investments), and (ii) different levels of coordination among market participants. Hence, we can assess the benefits of various coordination strategies against the actual approach to system expansions with no coordination among developers. By running various case studies based on the Chilean electricity system by 2030, we show that recognition of socio-environmental externalities at the moment of deciding system expansions can have a significant impact on the location of future infrastructure and, remarkably, on the entire mix of new generation projects. Particularly, we found an increase in bulk, transmission-connected solar power generation capacity by circa 25% when land-use externalities are considered in the system expansion problem. This is so because bulk solar power generation projects tend to present less socio-environmental impacts (since the solar power potential is generally higher in deserts and arid regions, away from populated areas) and, up to a certain extent, have the ability to displace the need for other generation technologies, particularly hydropower, located in areas with significantly conflicting land uses. We also demonstrated the benefits of investment coordination in supporting both an increased penetration of solar power generation, and an economically effective and sustainable development of a low-carbon power system in Chile.